2022
DOI: 10.1039/d1ta10125k
|View full text |Cite
|
Sign up to set email alerts
|

Relieving hydrogen evolution and anodic corrosion of aqueous aluminum batteries with hybrid electrolytes

Abstract: The lower electro-stripping/plating potential of Al3+/Al (-1.68V) than that of H+/H2 seriously impedes the performance of rechargeable aqueous aluminum-ion batteries (AAIBs). Besides, the Al plate is easily being corroded in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…9,[18][19][20] An Al-Zn ion battery with Al 2 (SO 4 ) 3 /Zn(CHCOO) 2 as a hybrid electrolyte was reported to have an energy density of 40 W h kg À1 aer 200 cycles, 21 but the cycle performance and capacity retention rates were not satisfactory. Similarly, Li et al reported that a full aqueous aluminum ion battery composed of a vanadium potassium cathode and Al anode exhibited reversible charge/discharge behaviors in 0.5 M AlCl 3 @12 M LiTFSI electrolyte, 22 while the battery cycling stability was only 64.6% aer 300 cycles. Therefore, it is critical to pursue a hybrid-ion system to assist AAIBs with long cycle life and high energy density.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…9,[18][19][20] An Al-Zn ion battery with Al 2 (SO 4 ) 3 /Zn(CHCOO) 2 as a hybrid electrolyte was reported to have an energy density of 40 W h kg À1 aer 200 cycles, 21 but the cycle performance and capacity retention rates were not satisfactory. Similarly, Li et al reported that a full aqueous aluminum ion battery composed of a vanadium potassium cathode and Al anode exhibited reversible charge/discharge behaviors in 0.5 M AlCl 3 @12 M LiTFSI electrolyte, 22 while the battery cycling stability was only 64.6% aer 300 cycles. Therefore, it is critical to pursue a hybrid-ion system to assist AAIBs with long cycle life and high energy density.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, it is critical to pursue a hybrid-ion system to assist AAIBs with long cycle life and high energy density. 15,17,[22][23][24][25] In this work, we demonstrate the enhancement of the energy density of AAIBs through the surface reaction of iron pairs in a newly developed electrolyte, i.e. a hybrid-ion aqueous aluminum ion battery (HIAAIB).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mo, V, or Ti as the active transition metals have together with IL based electrolytes provided specific cell energy densities of 60-120 W h kg À1 , [21][22][23] while inorganic cathodes based on V or Mn and aqueous electrolytes have yielded ca. 225 24 and 370 [25][26][27] W h kg À1 , respectively. Although this may sound remarkable, the (very) strong interactions between the Al 3+ ions and the cathode hosts result in high charging over-potentials and hence low energy efficiencies of ca.…”
Section: Introductionmentioning
confidence: 99%